Genome-wide identification and comprehensive analysis heat shock transcription factor (Hsf) members in asparagus (Asparagus officinalis) at the seeding stage under abiotic stresses - Li, Caihua; Li, Yuhuan; Zhou, Zeng; Huang, Yudi; Tu, Zunzun; Zhuo, Xin; Tian, Dingyuan; Liu, Yibo; Di, Hongli; Lin, Ze; Shi, Mingxin; He, Xue; et al. (Scientific reports, 2023)
Heat shock transcription factors (Hsf) are pivotal as essential transcription factors. They function as direct transcriptional activators of genes regulated by thermal stress and are closely associated with various abiotic stresses. Asparagus ( Asparagus officinalis ) is a vegetable of considerable economic and nutritional significance, abundant in essential vitamins, minerals, and dietary fiber. Nevertheless, asparagus is sensitive to environmental stresses, and specific abiotic stresses harm its yield and quality. In this context, Hsf members have been discerned through the reference genome, and a comprehensive analysis encompassing physical and chemical attributes, evolutionary aspects, motifs, gene structure, cis -acting elements, collinearity, and expression patterns under abiotic stresses has been conducted. The findings identified 18 members, categorized into five distinct subgroups. Members within each subgroup exhibited analogous motifs, gene structures, and cis -acting elements. Collinearity analysis unveiled a noteworthy pattern, revealing that Hsf members within asparagus shared one, two, and three pairs with counterparts in Arabidopsis, Oryza sativa, and Glycine max, respectively.Furthermore, members displayed tissue-specific expression during the seedling stage, with roots emerging as viable target tissue. Notably, the expression levels of certain members underwent modification under the influence of abiotic stresses. This study establishes a foundational framework for understanding Hsf members and offers valuable insights into the potential application of molecular breeding in the context of asparagus cultivation.